This is my dollhouse - Potter, Giselle (Schwartz & Wade Books, 2016)
A little girl who has made her own dollhouse from a box and her vivid imagination has trouble playing with her friend Sophie's perfect dolls and dollhouse, but when Sophie comes to visit she is afraid that her handiwork will not be good enough for Sophie.